MO040LONG-TERM FOLLOW-UP OF IGA NEPHROPATHY PATIENTS AT HIGH RISK OF PROGRESSION ACCORDING TO THE THERAPEUTIC APPROACH EMPLOYED: A MULTICENTER RETROSPECTIVE STUDY OF 947 PATIENTS. (6th June 2020) - Alberici, Federico; Baragetti, Ivano; Ferrario, Francesca; Ponti, Serena; Salviani, Chiara; Del Vecchio, Lucia; Viazzi, Francesca; Pani, Antonello; Manno, Carlo; Boscutti, Giuliano; Di Cesare, Grazia; Pozzi, Claudio
Abstract: Background and Aims: IgA-nephropathy (IgA-N) is a frequent cause of CKD and ESRD. The optimal therapeutic approach and the role of glucocorticoids and immunosuppression is still debated. Aim of this study was to perform a survey across several Italian centers focusing on the long-term outcome of patients with IgA-N at high risk of progression stratified according to the therapeutic approach employed. Method: All the consecutive patients affected by biopsy proven IgA-N, proteinuria >1g/day and a follow-up longer than 24 months have been collected across 48 centers. The population has been divided in three groups according to the therapeutic approach: group-1 received ACEi or ARBs alone, group-2 a six months course of glucocorticoids while group-3 glucocorticoids and immunosuppressive drugs. Primary endpoints have been ESRD free-survival, halving of the eGFR free-survival and rate of non-responders (NR, proteinuria >1 g/day). Secondary endpoints have been assessment of the prognostic role of the time average proteinuria (TAP) as well as of the time average slope of proteinuria (TASP) and rate of severe adverse events (SAEs). Results: 947 patients have been included and followed for a median time of 60 months (IQR 24-96). Baseline eGFR and proteinuria in the three groups have been respectively 68.1 (95%CI 63.9-72.4)-67.8 (95%CI 65.3-70.3)-63.3 (95%CI 58.5-68.1) ml/min/1.73m2 (p=0.191) and 2.38 (95%CI 2-2.77)-2.65 (95%CI 2.49-2.82)-3.26 (95%CI 2.89-3.64) g/day (p<0.001). Respectively 76/586 (13%) and 28/167 (17%) of the patients in group-2 and 3 required re-treatment with glucocorticoids alone or in combination with immunosuppressive drugs after a median of 24 months from the first cycle. ESRD free-survival has been longer in the group-2 (p=0.004) ( figure, panel A ); at subgroup analysis this was restricted to the patients with a eGFR<50 ml/min (p=0.004) ( figure, panel B ) while only a trend was observed in the ones with eGFR ≥50 ml/min (p=0.0631). The halving of the eGFR free-survival has been longer in group-2 only when limiting the analyses to the subgroup with eGFR<50 ml/min (p=0.026) ( figure, panel C ). The proportion of NR has been significantly lower in group-2 compared to group-1 throughout the first 36 months of follow-up ( figure, panel D ); of note being NR during the first 36 months increased the risk of developing ESRD during the follow-up (OR 4 95%CI 2.2-7.3, p<0.0001). The TAP and TASP of the first 24 months have been higher in the patients developing ESRD (respectively, mean 2.48 95%CI 2.14-2.82 and 0.81 95%CI 0.70-0.92) compared to the other patients (mean 1.12 95%CI 1.2-1.32 and 0.59 95%CI 0.56-0.61) (p<0.0001 for both comparisons). Of note the 24 months TASP of group-2 was lower compared to group-1 (respectively mean 0.56 95%CI 0.54-0.59 and 0.79 95%CI 0.71-0.87) (p<0.0001). The rate of patients experiencing SAEs during the first 6 months of therapy in the three groups has been respectively 2%, 7% and 16%; of these withdrawn of the therapeutic approach employed has been necessary in 67%, 21% and 48%. During the whole follow-up the number of SAEs per 100 patients/years has been respectively 1.9-2.7 and 2.5 in the 3 groups. Conclusion: In this large multicenter retrospective survey, the use of glucocorticoids in patients with IgA-N at high risk of progression has been associated to longer ESRD free-survival, longer time to the halving of the eGFR in the subgroup with eGFR <50 ml/min, lower rate of non-response during the first 36 months of follow-up as well as lower TASP during the first 24 months. The overall rate of SAEs has been low but higher in the group receiving glucocorticoids alone or in combination with immunosuppressors.